Basic Issues in Evaluation of Training Programmes - Y. A. Oguntimehin; A. O. Bukki (University of Sofia, 2020)
Evaluation is mainly carried out to avoid any fiscal educational programmes irresponsibility so as to enhance educational quality output. Since evaluation requires the process of carrying out investigation into success progress or otherwise of an existing practice procedure in an organisation, it becomes very necessary for all educational managers/leaders to know what evaluation is, why it is very important and how it can be properly carried out so as to achieve desired goals and objectives. This paper, therefore, focuses on the concept, types, aims, models and guiding principles of evaluation.